Regional payment systems: A comparative perspective on Europe and the developing world - Barbara Fritz; André Biancareli; Laurissa Mühlich (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2012)
The current global financial non-system is marked by instability. In the absence of global solutions, a series of regional arrangements of monetary cooperation have been emerging to cope with such instability. The paper focuses on regional payment systems as an initial step of regional monetary cooperation. In order to evaluate their potential contribution to increase macroeconomic stability of the member countries, we develop a typology of payments systems and systematically compare historic and present initiatives in Europe, Asia and Latin America with reference to the original Keynes Plan. We show that regional payment systems entail beneficial effects by reducing transaction costs of intraregional trade, and by creating incentives for further macroeconomic cooperation. Their contribution to macroeconomic stabilization however depends on the specific design of the respective regional arrangement.
Keywords: 330; Internationaler Zahlungsverkehr; Internationales Währungssystem; Handelsregionalismus; Wirtschaftliche Instabilität; Europa; Asien; Lateinamerika